Intelligent vehicle technology and trends - Bishop, Richard, 1958- (Artech House ITS library., 2005)
"This resource offers professionals a comprehensive overview of cutting-edge intelligent vehicle (IV) systems aimed at providing enhanced safety, greater productivity, and less stress for drivers. Rather than bogging readers down with difficult technical discourse, this easy-to-understand book presents a conceptual and realistic view of how IV systems work and the issues involved with their introduction into road vehicles."--Jacket